2016
DOI: 10.1007/s00170-016-9396-4
|View full text |Cite
|
Sign up to set email alerts
|

MQL with water in cylindrical plunge grinding of hardened steels using CBN wheels, with and without wheel cleaning by compressed air

Abstract: Minimum quantity of lubricant (MQL) in grinding is an alternative for reducing abundant fluid flow and both environmental and health hazards when compared with conventional fluid application. In spite of the fact that MQL is considered an innovative cost-effective and environmentally friendly technique, when used in grinding its inadequate application can increase cutting temperature and wheel clogging, worsening surface roughness, and increasing geometric and dimensional errors. The present study aims to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Moreover, the material used (AISI 1020) is a soft steel and does not influence wheel wear. Reliable results using this method were obtained in [19][20][21][22].…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Moreover, the material used (AISI 1020) is a soft steel and does not influence wheel wear. Reliable results using this method were obtained in [19][20][21][22].…”
Section: Methodsmentioning
confidence: 87%
“…In order to further improve the efficiency of MQL technique, Ruzzi et al [22] used a cleaning air jet combined with oil-water MQL. They ground a hardened steel with a CBN grinding wheel and found that the addition of water made it easier for the cutting fluid to penetrate wheel pores and the cutting zone, promoting a more intensive reduction of clogging effect and, as a consequence, of surface roughness and roundness deviation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to researches carried out by Malkin and Guo [7], Marinescu et al [13] and Ruzzi et al [19] in grinding of hardened steels with conventional abrasive grinding wheels, higher the feed rate, the higher and faster is the advancement of grinding tool against the workpiece. On this way, the surface roughness increases because of the higher cutting forces that are generated by the faster advancement of the grinding wheel moving at higher infeed rate, thereby promoting vibrations and leading to deterioration of the surface finish [20].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…When the lubrication property of cooling-lubrication technique is reduced, grinding forces increase, then more power is required to perform cutting. Ruzzi et al [31] reported that the when a cooling capacity in grinding of hardened steel with conventional abrasive wheel is achieved, the workpiece material temperature will be kept in lower levels, so its mechanical resistance will be retained, which in turn, hampers the cutting action by the wheel grits, thereby requiring higher grinding power.…”
Section: Grinding Powermentioning
confidence: 99%